Avaliação das perdas de solos por erosão laminar na área de influência da UHE Amador Aguiar I - Pereira, Juliana Sousa (2014)
Soil erosion is a natural process of the morphogenesis of strands and continually happens on the earth\'s surface. The onset of erosion depends on the interaction of influential variables in the process, as the rainfall erosivity, soil property, plant cover, slope characteristic and soil management. The sheet erosion; is caused when the energy of the flow surface is larger than the cohesive forces which keep soil particles together. This type of erosion happen in a diffuse manner without developing visible channeled flow, however, may cause significant loss of soil during a single rainfall event. This study aimed to estimate soil loss by sheet erosion in the catchment area of UHE Amador Aguiar I, inserted into Araguari River Basin-MG through the Universal Soil Loss Equation model (USLE). Mathematical models of erosion have been proven effective in quantitative and qualitative assessment of soil losses, with relevance in predictive modeling of agricultural areas and also areas with reservoirs for water exploration. In this context, the use of these models, along with the field investigation of variables evaluated, brings an important contribution to the diagnosis of a watershed. The USLE combined with a Geographic Information System - GIS enables the quantification of losses from soils under various physiographic conditions. The calculation of the annual soil loss for the study area was achieved through the elaboration of thematic maps of the components of USLE, namely: Factor R; Factor K; factor LS; Factor C and Factor P. The components of USLE were evaluated on an individual basis, in this context, the annual erosivity average for the area is approximately 8881.9 MJ.mm.ha-1 year-1, considered high according to the classification of Mello et al. (2007). Latossolos have medium to high erodibility (K factor), while the Argissolos and Cambissolos have very high erodibility, above 0,051 t.ha.h / ha.MJ.mm. These recent pedological types are distributed in patches of relief with steep slopes, in an area of Canyon, showing great susceptibility to water erosion. The topographic factor (LS) showed large variations, reaching values higher than 80, due to the predominance of steep slopes near the bottom of Araguari River valley. In the study area pastures have greater coverage, however, the land use is also characterized by areas of woody vegetation and agriculture. Accordingly, for the vegetation cover (Factor C) classes adopted were: 0 (soil protection) and 1 (soil without protection), moreover the conservation regarding practices (P factor), values ranged from 0 to 0.5 respectively. The annual estimated rate of erosion varies according to the physiographic features of the area, reaching the maximum of 23,5 t.ha-¹.year-¹. in the perspective, this study may contribute to the management bodies of de basin, since it will indicate the amount of soil loss simultaneously highlighting the areas most susceptible to sheet erosion.